Risk-Sharing Networks in Rural Philippines. - Fafchamps, M; Lund, S (2003)
Using detailed data on gifts, loans, and asset sales, this paper investigates how rural Filipino households deal with income and expenditure shocks. We find that shocks have a strong effect on gifts and informal loans, but little effect on sales of livestock and grain. Mutual insurance does not appear to take place at the village level; rather, households receive help primarily through networks of friends and relatives. Certain shocks are better insured than others. The evidence is consistent with models of quasi-credit where risk is shared within networks through flexible, zero-interest informal loans combined with pure transfers.